Digital Technology Usage in Undergraduate Students at a Medical College of Nepal - Jha , Jay Prakash; Joshi, Bishal (Journal of College of Medical Sciences-Nepal, 2025)
Background The ubiquitous use of digital gadgets is changing the teaching-learning methods in medical education. This study aims to assess the patterns of electronic device and internet use among undergraduate medical students; and to explore their preferences, digital literacy, and use of various online and traditional study resources in their education. Methods This cross-sectional descriptive study was conducted among 122 medical students at Universal College of Medical Sciences, Lumbini, Nepal using enumerative sampling. A self-administered questionnaire was used to collect data on sociodemographic characteristics, electronic device and internet use patterns, and its use in their study. Data were analysed by descriptive statistics. Results Among 122 participants, most were female (82.78%), with a mean age of 20 (range 17-26) years. Almost all students used smartphones regularly, spending an average of 4.27 hours on weekdays and 6.86 hours on holidays on devices. Social media was the primary use of smartphones. Most students had moderate level of knowledge and interest in computer technology, but 11 students expressed high interest in learning despite low knowledge. For medical study, conventional textbooks and online videos were most popular modes. More than half (59%) expressed the benefit of having online contact with teachers. Conclusions Health science students of the medical college rely heavily on electronic devices and social media in daily life as well as for studies; highlighting the need to integrate technology-based learning strategies into medical education curricula.